If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 4 + -2y Solving 3 = 4 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 3 + 2y = 4 + -2y + 2y Combine like terms: -2y + 2y = 0 3 + 2y = 4 + 0 3 + 2y = 4 Add '-3' to each side of the equation. 3 + -3 + 2y = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 4 + -3 2y = 4 + -3 Combine like terms: 4 + -3 = 1 2y = 1 Divide each side by '2'. y = 0.5 Simplifying y = 0.5
| 1=4-2y | | 3(3x+2)=11x+4-2x+2 | | (1*2x)+(1*x)=12 | | (1.2*2x)+(0.8*x)=12 | | 2x(x+2)(x+6)=0 | | (1.2*2x)+(0.8*x)=6 | | Factorizem^3+5m^2=0 | | 1.2*2x+0.8*x=6 | | 7x+5y=115x+7y=13findx+y | | 2x^2+5x-k=0 | | 4y+Z-23=40 | | Y=50-1.5(10) | | 6y+2y-2=180 | | 8x+27x-9=7(5x+9) | | p+80=9p | | p+4=3p | | 3v+58=v+78 | | 2z=z+28 | | u+38=3u | | 3t=t+54 | | c+15=2c | | 6x^2+6x-12= | | 3t=t+32 | | 4q=q+15 | | 3m-1/4-2m-2/3=1 | | u+19=2u | | q+56=5q | | 240-1.6x=0 | | ([x^2+3]+[x-5])(6)= | | (x^2+3+x-5)(6)= | | (5v+3)(9+v)= | | 6x^3/24x^4 |